Therapeutic potential of extracellular vesicles derived from Platycladus Orientalis leaf in treating anxiety, depression, and insomnia - Liu, Peiyu; He, Guiyang; Lu, Yaoxin; He, Juanjuan; Wu, Faliang; Jia, Meng; Jia, Shaochang; Fan, Ruijie; Liang, Hongwei; Liu, Bing; Li, Min (Frontiers in Pharmacology, 2025)
ObjectivesExtracellular vesicles (EVs) mediate intercellular communication by transferring bioactive molecules. While animal-derived EVs are well studied, plant-derived EVs (plant-EVs) are emerging as stable, low-immunogenic nanocarriers with therapeutic potential. Platycladus orientalis (L.) Franco, used in traditional medicine, contains neuroactive compounds. This study evaluated the effects of P. orientalis leaf-derived EVs in rodent models of anxiety, depression, and insomnia.MethodsEVs were isolated by differential ultracentrifugation, characterized by electron microscopy and nanoparticle tracking analysis, and their bioactive components identified by GC -MS. Uptake was assessed in PC12 cells. Behavioral and biochemical effects were tested in mice subjected to chronic restraint stress (CRS), chronic unpredictable mild stress (CUMS), and para-chlorophenylalanine (PCPA)-induced insomnia. Key outcomes included social interaction, sucrose preference, Morris water maze performance, sleep parameters, neurotransmitter levels (5-HT, GABA), and inflammatory markers.ResultsP. orientalis EVs exhibited bilayer vesicle morphology (∼100 nm) and contained abundant volatile compounds, particularly α-pinene. They were internalized by PC12 cells and reduced corticosterone-induced injury. In vivo, intranasal EV administration alleviated anxiety-like behaviors in CRS mice, restored sucrose preference and cognition in CUMS mice, and improved sleep onset and duration in PCPA-induced insomnia. Across models, EVs normalized serum and hippocampal 5-HT and GABA levels, reduced pro-inflammatory cytokines (TNF-α, IL-6), and increased TGF-β expression.ConclusionP. orientalis leaf-derived EVs exert significant anxiolytic, antidepressant, and soporific effects through multimodal mechanisms involving neurotransmitter regulation and anti-inflammatory activity. Intranasal administration offers an effective strategy to bypass the blood -brain barrier, supporting the translational potential of plant-EVs as novel therapeutics for psychiatric disorders.